The State-of-the-Art of Gene Editing and its Application to Viral Infections and Diseases Including COVID-19 - Hawsawi, Yousef M.; Shams, Anwar; Theyab, Abdulrahman; Siddiqui, Jumana; Barnawee, Mawada; Abdali, Wed A.; Marghalani, Nada A.; Alshelali, Nada H.; Al-Sayed, Rawan; Alzahrani, Othman; Alqahtani, Alanoud; Alsulaiman, Abdulrahman M. (Frontiers in Cellular and Infection Microbiology, 2022)
Gene therapy delivers a promising hope to cure many diseases and defects. The discovery of gene editing technology fueled the world with valuable tools that employed in various domains of science, medicine, and biotechnology. Various tools of gene editing have been established, this include CRISPR, ZFNs and TALENs. These strategies are believed to help in understanding the biological mechanisms of disease progression. Severe acute respiratory syndrome coronavirus (SARS-CoV-2) designated as a causative virus for coronavirus disease 2019 (COVID-19) that emerged at the end of 2019. This viral infection is highly pathogenic and transmissible disease caused a public health pandemic. As gene editing tools have shown a great success in multiple scientific and medical areas, they could eventually contribute to the discovery of novel therapeutics and diagnostics strategies to battle COVID-19 pandemic infection. This review aims to briefly highlight the history and some of the recent advancements of gene editing technologies. Thereafter, we will focus on describing various biological features of CRISPR-Cas9 system and its diverse implications in the treating different diseases both viral and non-viral conditions. Finally, we will present the current and future advancements in combating COVID-19 with potential contribution of the CRISPR system as antiviral modality in this battle.